Literature Review: The Role of Ajwa Dates (Phoenix Dactylifera L.) as a Natural Phytoestrogen in Reducing Perimenopause Symptoms - Fitra Amalia Salsabila; Nasrudin Andi Mappaware; Haeriyanty Haeriyanty (Newinera Publisher, 2026)
Perimenopause is a transitional phase before menopause characterized by a decrease in estrogen levels and the appearance of symptoms such as hot flushes, sleep disturbances, and mood changes. One natural alternative to reduce these symptoms is the use of phytoestrogens, which are plant compounds that mimic estrogen hormones. Ajwa dates (Phoenix dactylifera L.) contain flavonoids, phenolics, saponins, and phytoestrogens that have the potential to help balance hormones and reduce perimenopausal symptoms. This study aims to examine the role of Ajwa dates as a natural phytoestrogen in alleviating perimenopausal symptoms. This study employed a literature review design with a narrative approach. Data were obtained from five relevant national and international journals, with inclusion criteria covering studies discussing the role of Ajwa dates as a natural phytoestrogen in reducing perimenopausal symptoms. The data sources were analyzed qualitatively to assess the relationships between variables and the conclusions of the studies. The review results indicate that consumption of Ajwa dates can increase Anti-Mullerian Hormone (AMH) and Follicle Stimulating Hormone (FSH) levels, improve the number of de Graaf follicles, and thicken the endometrium. In vitro studies also show that Ajwa date extracts have significant antioxidant and phytoestrogenic activities. These effects contribute to improved ovarian function and the reduction of clinical symptoms caused by estrogen deficiency in perimenopausal women. Ajwa dates play an important role as a natural phytoestrogen capable of reducing perimenopausal symptoms through mechanisms such as hormonal balance improvement, antioxidant activity, and ovarian function enhancement.